2013
DOI: 10.1051/0004-6361/201322319
|View full text |Cite
|
Sign up to set email alerts
|

The importance of non-photon noise in stellar spectropolarimetry

Abstract: Context. The low-resolution, Cassegrain mounted, FORS spectropolarimeter of the ESO Very Large Telescope is being extensively used for magnetic field surveys. Some of the new discoveries suggest that relatively strong magnetic fields may play an important role in numerous physical phenomena observed in the atmospheres as well as in the circumstellar environments of certain kinds of stars. Aims. We show in detail how small instabilities or data-reduction inaccuracies represent an alternative explanation for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(81 citation statements)
references
References 28 publications
6
72
3
Order By: Relevance
“…seeing variations during very short exposures (Bagnulo et al , 2013. In general we found that our error estimates were higher than those published in previous works.…”
Section: Error Estimationcontrasting
confidence: 59%
“…seeing variations during very short exposures (Bagnulo et al , 2013. In general we found that our error estimates were higher than those published in previous works.…”
Section: Error Estimationcontrasting
confidence: 59%
“…These problems have been thoroughly discussed by Bagnulo et al (2012) and Bagnulo et al (2013), and a discussion on the quality of the non-controversial FORS1 measurements of magnetic Ap stars was presented by Landstreet et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…For the first reduction, we used a suite of IRAF (Tody 1993) 1 and IDL routines that follow the technique, recipes, and recommendations by Bagnulo et al (2002Bagnulo et al ( , 2012Bagnulo et al ( , 2013 2 . The determination of the mean longitudinal magnetic field using low-resolution FORS spectropolarimetry with the second software package developed in Potsdam is described by Hubrig et al (2014Hubrig et al ( , 2015 and by Schöller et al (in prep.).…”
mentioning
confidence: 99%